PACKAGING CONTAINERS - NAIR, Hariharan Krishnan (2025)
The present subject matter related to packaging containers (100). In an example, the packaging container (100) includes a hollow body (102) having a top end (108) and a bottom end (110). The hollow body (102) 5 includes a first opening (112) at the top end (108) and a second opening (114) at the bottom end (110) and is fillable with a material via the first opening (112). The hollow body (102) is closable by closing means. La présente invention concerne des contenants d'emballage (100). Dans un exemple, le contenant d'emballage (100) comprend un corps creux (102) ayant une extrémité supérieure (108) et une extrémité inférieure (110). Le corps creux (102) comprend une première ouverture (112) au niveau de l'extrémité supérieure (108) et une seconde ouverture (114) au niveau de l'extrémité inférieure (110) et peut être rempli d'un matériau par l'intermédiaire de la première ouverture (112). Le corps creux (102) peut être fermé par des moyens de fermeture.